2010
DOI: 10.1002/jbmr.305
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of teriparatide on regional bone formation using 18F-fluoride positron emission tomography

Abstract: Teriparatide increases skeletal mass, bone turnover markers, and bone strength, but local effects on bone tissue may vary between skeletal sites. We used positron emission tomography (PET) to study 18 F-fluoride plasma clearance (K i ) at the spine and standardized uptake values (SUVs) at the spine, pelvis, total hip, and femoral shaft in 18 postmenopausal women with osteoporosis. Subjects underwent a 1-hour dynamic scan of the lumbar spine and a 10-minute static scan of the pelvis and femurs at baseline and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 39 publications
4
70
1
Order By: Relevance
“…In agreement with a previous single-arm study of postmenopausal women with osteoporosis treated with TPT for 6 months by the same authors, (23) percentage changes in K i were greatest at the hip (Table 2, Fig. 3).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In agreement with a previous single-arm study of postmenopausal women with osteoporosis treated with TPT for 6 months by the same authors, (23) percentage changes in K i were greatest at the hip (Table 2, Fig. 3).…”
Section: Discussionsupporting
confidence: 92%
“…The early timing of the DXA scan limits any useful comparison with other studies, but results from the pivotal fracture trials of TPT showed that changes in areal BMD are greatest at the lumbar spine, with only relatively modest gains or even loss in BMD being seen at the hip. (35)(36)(37)(38) As observed in an earlier 6-month study of the effect of TPT treatment at the lumbar spine, (23) there was a disparity between the changes in regional bone formation and results from studies of the effects of teriparatide on BMD at the spine and hip. (35)(36)(37)(38)(39) The increases in BMD at the hip are relatively modest compared with those observed at the lumbar spine.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations